Franciscana (Pontoporia blainvillei) found dead in Northern Patagonia, Argentina: record, description and sampling. Preliminary report - Winter, Marina (2021)
Fil: Winter, Marina. Universidad Nacional de Río Negro. Centro de Investigaciones y Transferencia de Río Negro. Río Negro, Argentina.